Reimagining inclusive mathematics education in Ghana through ethnomathematics - Bright Asare (Frontiers in Psychology, 2026)
This study investigates the integration of ethnomathematics into Ghana's mathematics curriculum as a pathway to achieving inclusive and culturally responsive education. Despite multiple post-independence curriculum reforms, mathematics education in Ghana remains predominantly influenced by Western paradigms, often neglecting the rich indigenous mathematical knowledge embedded in the country's diverse cultural practices. This disconnects between formal schooling and the lived experiences of learners, particularly in rural and marginalized communities, contributes to low engagement, limited comprehension, and reduced academic confidence. Grounded in theories of Culturally Responsive Pedagogy, Social Constructivism, and Funds of Knowledge, the study critically examines the extent to which the current curriculum, teacher practices, and instructional resources reflect local knowledge systems. Drawing on literature, policy documents, and curriculum analysis, the paper argues the need for policy reforms, teacher training, and the systematic inclusion of ethnomathematics to foster equity, relevance, and engagement in mathematics classrooms. Ultimately, the study advocates for a culturally affirming and inclusive curriculum that bridges the gap between school mathematics and Ghana's sociocultural realities, aligning with the goals of Sustainable Development Goal 4 and Ghana's Education Strategic Plan 2018–2030.